In the shadow of the Han : literati thought and society at the beginning of the Southern dynasties - Holcombe, Charles, 1956- (University of Hawaii Press, 1994)
Falling between the great unified empires of the Han and T'ang, the Period of Division (A.D. 220-589) is one of the most overlooked and least understood eras in Chinese history. At the start of the fourth century much of China's traditional heartland fell under the control of ethnic non-Chinese. The remnants of the Chinese court fled to the still somewhat exotic region south of the Yangtze River, where an Eastern Chin dynasty (318-420) was established in virtual exile. The state's ability to command population and other resources had declined sharply from the heights of Han imperial splendor, but it retained considerable influence over most aspects of society, including the economy. This residual state power made possible the rise, through the monopolization of government office, of a new elite class - the literati, or shih-ta-fu.
Keywords: China -- History -- Northern and Southern dynasties, 386-589.; Chine -- Histoire -- 386-589 (Dynasties du Nord et du Sud); HISTORY.; HISTORY -- Asia -- General.; Northern and Southern Dynasties (China); China; Chinees.; Cultuurgeschiedenis.; Chine -- Histoire -- 386-589 (dynastie du Nord et du Sud); 386-589; History